2008
DOI: 10.1302/0301-620x.90b5.20546
|View full text |Cite
|
Sign up to set email alerts
|

Is return to professional rugby union likely after anterior cervical spinal surgery?

Abstract: We have examined the outcome in 19 professional rugby union players who underwent anterior cervical discectomy and fusion between 1998 and 2003. Through a retrospective review of the medical records and telephone interviews of all 19 players, we have attempted to determine the likelihood of improvement, return to professional sport and the long-term consequences. We have also attempted to relate the probability of symptoms in the neck and radicular pain in the arm to the position of play. Neck and radicular pa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
32
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 31 publications
(33 citation statements)
references
References 6 publications
(3 reference statements)
1
32
0
Order By: Relevance
“…Several authors have reported through experiential guidelines and management algorithms that there is no contraindication to RTP after a single-level anterior cervical fusion if an individual has a solid arthrodesis, absence of neurological deficits, and normal cervical range of motion. [3][4][5][6][7][8][9][10]24,29 Overall, these recommendations are primarily based on expert opinion resulting from clinical experience and indirect literature on the topic. In 1997, Torg and Ramsey-Emrhein 8 set forth one of the earliest recommendations regarding RTP in the setting of cervical fusion.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Several authors have reported through experiential guidelines and management algorithms that there is no contraindication to RTP after a single-level anterior cervical fusion if an individual has a solid arthrodesis, absence of neurological deficits, and normal cervical range of motion. [3][4][5][6][7][8][9][10]24,29 Overall, these recommendations are primarily based on expert opinion resulting from clinical experience and indirect literature on the topic. In 1997, Torg and Ramsey-Emrhein 8 set forth one of the earliest recommendations regarding RTP in the setting of cervical fusion.…”
Section: Discussionmentioning
confidence: 99%
“…10 This study retrospectively reviewed 19 professional rugby players who underwent ACDFs over a 5-year period. The aim of the study was to assess the safety and efficiency of ACDF in a high-energy contact sport setting and to document whether athletes were able to RTP.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…After 2-reviewer assessment, 6 articles were identified that met all of the inclusion criteria. [10][11][12][13][14][15] One study was excluded as the methodology of the article relied on an analysis of team injury reports and newspaper archives, and not on the direct treatment of players. 12 The 5 studies that were selected for inclusion were all retrospective case series.…”
Section: Systematic Reviewmentioning
confidence: 99%
“…[10][11][12][13][14][15] While these studies have provided some guidance on the ability to return to play after ACDF, most of the data is from small retrospective case series.…”
Section: Introductionmentioning
confidence: 99%